AMNESTY AND THE OBLIGATIO ERGA OMNES TO REPRESS HUMANITARIAN LAW VIOLATIONS: LESSONS FROM THE SIERRA LEONE CONFLICT - Ndifon, C. Osim (European Scientific Journal, ESJ, 2012)
The issue of the criminal liability of individuals in both their personal and official capacities is central to human rights adjudication. But this notion becomes a farce if states grant to individuals certain immunities- such as amnesty, asylum or any other exculpating factors. The fact that amnesty have continued to be issued by various government makes it a compelling task for us to look at or determine its proper limits. Among the questions that may arise is: what is the extent of the powers of the government to grant amnesty, whether on a proper interpretation of state‟s responsibility to grant pardon for crimes committed against it vis-à-vis the duty under international law to punish those who have committed other crimes especially humanitarian law crimes. It is our argument that on a proper interpretation of this responsibility, states do not have an unlimited power to grant amnesty. States owe it as an obligation to its citizens as well as to those within its bodies to bring to book perpetrators of human rights abuse. The combination of the above mentioned factors therefore makes the issuance of amnesty asylum or any other exculpating factor, a total aberration. In this paper a background is given to the historical development of amnesty and the extent of states powers to confer same.